2021
DOI: 10.1161/atvbaha.120.315766
|View full text |Cite
|
Sign up to set email alerts
|

Overfeeding Saturated Fat Increases LDL (Low-Density Lipoprotein) Aggregation Susceptibility While Overfeeding Unsaturated Fat Decreases Proteoglycan-Binding of Lipoproteins

Abstract: Objective: We recently showed that measurement of the susceptibility of LDL (low-density lipoprotein) to aggregation is an independent predictor of cardiovascular events. We now wished to compare effects of overfeeding different dietary macronutrients on LDL aggregation, proteoglycan-binding of plasma lipoproteins, and on the concentration of oxidized LDL in plasma, 3 in vitro parameters consistent with increased atherogenicity. Approach and Results: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 74 publications
2
18
0
1
Order By: Relevance
“…However, a recent study showed that overfeeding of carbohydrates increases levels of TG-SFAs, and decreases TG-PUFAs in LDL lipids, with no change in TG-MUFAs. Also, a high fat diet was found to have a similar, but stronger impact [ 48 ]. Since glimepiride administration did result in decreased TGs overall, and the difference between liraglutide and glimepiride treatments was mainly in TG-MUFA, it is unlikely that dietary factors had a major impact on the observed metabolic changes between the two treatments.…”
Section: Discussionmentioning
confidence: 99%
“…However, a recent study showed that overfeeding of carbohydrates increases levels of TG-SFAs, and decreases TG-PUFAs in LDL lipids, with no change in TG-MUFAs. Also, a high fat diet was found to have a similar, but stronger impact [ 48 ]. Since glimepiride administration did result in decreased TGs overall, and the difference between liraglutide and glimepiride treatments was mainly in TG-MUFA, it is unlikely that dietary factors had a major impact on the observed metabolic changes between the two treatments.…”
Section: Discussionmentioning
confidence: 99%
“…In agreement with these overfeeding studies [38,39,43], a study of 2860 Chinese Singaporeans showed that higher saturated fat intake was associated with higher concentrations of specific sphingolipids, including ceramides, monohexosylceramides, dihexosylceramides, SMs, and sphingosine-1-phosphates [45]. Higher intake of PUFAs or proteins was shown to have an opposite effect.…”
Section: Impact Of Healthy Diet On Lipidomementioning
confidence: 62%
“…To elucidate how the overfeeding impacts the metabolic health, a study conducted in Finland explored differences in plasma lipidome and lipoprotein profile of individuals subjected to overfeeding for 3 weeks (addition of 1000 kcal/day) with either unsaturated fat, saturated fat or simple sugars [38,39]. In contrast to unsaturated fat, overfeeding with saturated fat led to increase in intrahepatic triacylglycerols and increase in plasma ceramide levels [38].…”
Section: Obesity and Overfeeding: The Type Of Fats And Sugar Mattersmentioning
confidence: 99%
“…In this regard, a pilot study in 6 hypertriglyceridemic men showed that the supplementation for 8 weeks with 3 g/d fish oil rich in EPA and DHA decreased fasting TG in plasma and large VLDL but also Cer concentrations in VLDL, without any modification of SM concentrations in VLDL ( 35 ). Regarding LDL, a dietary intervention study comparing the effects of different types of fats on plasma lipoproteins in 36 overweight middle-aged subjects showed that a 3-week consumption of extra daily 1,000 kCal coming from SFA resulted in modifications of LDL composition, independently of LDL cholesterol ( 36 ). Excess consumption of SFA (30 g coconut oil, 40 g butter, 100 g blue cheese 40% fat), but not unsaturated fats (36 g olive oil, 266 g pesto, 54 g pecan nuts, 20 g butter), increased concentrations of SM, Cer and saturated TG in LDL and increased their susceptibility to aggregate and consequently their atherogenicity.…”
Section: Dietary Fatty Acids and Circulating Sphingolipidsmentioning
confidence: 99%